2018
DOI: 10.1111/jgh.13969
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a concomitant elemental diet to reduce the loss of response to adalimumab in patients with intractable Crohn's disease

Abstract: Concomitant ED therapy reduced ADA-LOR in IFX-intolerant or refractory patients in a dose-related manner. Reductions in the TNF-α levels by concomitant ED intake may contribute to reduce ADA-LOR in CD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
1
12
0
1
Order By: Relevance
“…EN does not directly induce an increase in anti-TNF-alpha antibody blood concentration or reduce antibody production. However, an increasing number of recent reports have shown how the use of EN in combination with an anti-TNF-alpha antibody is clinically useful due to the add-on effect of EN itself [40][41][42][43][44][45][51][52][53]. In the present review, in which these studies were meta-analyzed, the pooled OR for maintenance of remission or relapse with EN was 2.23 in the fixed effects model and 2.19 in the random effects model.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…EN does not directly induce an increase in anti-TNF-alpha antibody blood concentration or reduce antibody production. However, an increasing number of recent reports have shown how the use of EN in combination with an anti-TNF-alpha antibody is clinically useful due to the add-on effect of EN itself [40][41][42][43][44][45][51][52][53]. In the present review, in which these studies were meta-analyzed, the pooled OR for maintenance of remission or relapse with EN was 2.23 in the fixed effects model and 2.19 in the random effects model.…”
Section: Discussionmentioning
confidence: 54%
“…enteral nutrition vs conventional therapy: 1), and three articles where the end point was not clinical remission or response. Based on the results of these exclusions, nine articles meeting all criteria were included in this meta-analysis [40][41][42][43][44][45][51][52][53] (Fig. 1).…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this biologics era, the position of EN therapy has also changed. Recently, the combination use of anti-TNFα agents and EN therapy has been studied [92][93][94][95][96][97][98][99][100] (Table 2). Hirai et al [96] reported that EN combination group had better cumulative remission maintenance rate than IFX alone group in their retrospective analysis of patients with CD who received remission maintenance IFX therapy.…”
Section: (4) Sarcopeniamentioning
confidence: 99%
“…Nguyen et al [98] demonstrate that a combination of infliximab and EN is more effective at inducing and maintaining clinical remission among patients with CD than infliximab alone in a metaanalysis. Recently, it has also been reported with respect to efficacy of EN against loss of response to anti-TNFα agents [95,99,100] . and to remove antigenic mucosal stimuli [101] .…”
Section: (4) Sarcopeniamentioning
confidence: 99%